2021
DOI: 10.1371/journal.pone.0253118
|View full text |Cite
|
Sign up to set email alerts
|

Population-based incidence and mortality of community-acquired pneumonia in Germany

Abstract: Background Little information on the current burden of community-acquired pneumonia (CAP) in adults in Germany is available. Methods We conducted a retrospective cohort study using a representative healthcare claims database of approx. 4 million adults to estimate the incidence rates (IR) and associated mortality of CAP in 2015. IR and mortality were stratified by treatment setting, age group, and risk group status. A pneumonia coded in the primary diagnosis position or in the second diagnosis position with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 36 publications
2
26
1
5
Order By: Relevance
“…The Institute for Quality Assurance and Transparency in Healthcare (IQTIG) estimates there to be approximately 255,000 CAP cases annually in Germany (non-hospital acquired and in patients over 18 years) [ 3 ]. A study based on claims data recently published by Theilacker et al [ 4 ] also indicated high CAP incidence rates among adults in Germany; the authors reported an overall incidence rate of 1,054 cases per 100,000 person years of observation for the calendar year 2015. This study also revealed high mortality rates; 18.5% of patients ≥18 years hospitalized with CAP died during their inpatient stay, 22.9% died within 30 days and 44.5% died within one year following CAP onset [ 4 ].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The Institute for Quality Assurance and Transparency in Healthcare (IQTIG) estimates there to be approximately 255,000 CAP cases annually in Germany (non-hospital acquired and in patients over 18 years) [ 3 ]. A study based on claims data recently published by Theilacker et al [ 4 ] also indicated high CAP incidence rates among adults in Germany; the authors reported an overall incidence rate of 1,054 cases per 100,000 person years of observation for the calendar year 2015. This study also revealed high mortality rates; 18.5% of patients ≥18 years hospitalized with CAP died during their inpatient stay, 22.9% died within 30 days and 44.5% died within one year following CAP onset [ 4 ].…”
Section: Introductionmentioning
confidence: 93%
“…A study based on claims data recently published by Theilacker et al [ 4 ] also indicated high CAP incidence rates among adults in Germany; the authors reported an overall incidence rate of 1,054 cases per 100,000 person years of observation for the calendar year 2015. This study also revealed high mortality rates; 18.5% of patients ≥18 years hospitalized with CAP died during their inpatient stay, 22.9% died within 30 days and 44.5% died within one year following CAP onset [ 4 ]. CAP also has an impact on healthcare resources; Campling et al [ 5 ] found significantly higher healthcare resource utilization in patients with selected underlying comorbidities after hospitalization forCAP when compared to matched patients without CAP.…”
Section: Introductionmentioning
confidence: 93%
“…The burden imposed by community-acquired pneumonia (CAP) continues to be high in developed countries, especially among adults with underlying clinical risk conditions [ 1 , 2 ]. Incidence has seemingly been growing over the years, and the comorbidity of people affected by CAP needing hospital admission has been reported to be increasing across time [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pneumonia risk factors include low socioeconomic status, smoking, excessive alcohol consumption, chronic respiratory disease, chronic heart, liver and kidney diseases, autoimmune conditions, diabetes or haematological conditions, which are especially described among the elderly [ 8 15 ]. However, risk profiles for pneumonia among the young and working-age adult populations are not equally assessed [ 13 , 16 – 20 ].…”
Section: Introductionmentioning
confidence: 99%